Biostratigraphic and Geological Significance of Planktonic Foraminifera - BouDagher-Fadel, Marcelle K. (UCL Press, 2015)
The role of fossil planktonic foraminifera as markers for biostratigraphical zonation and correlation underpins most drilling of marine sedimentary sequences and is key to hydrocarbon exploration. The first - and only - book to synthesize the whole biostratigraphic and geological usefulness of planktonic foraminifera, Biostratigraphic and Geological Significance of Planktonic Foraminifera unifies existing biostratigraphic schemes and provides an improved correlation reflecting regional biogeographies. Renowned micropaleontologist Marcelle K. Boudagher-Fadel presents a comprehensive analysis of existing data on fossil planktonic foraminifera genera and their phylogenetic evolution in time and space. This important text, now in its Second Edition, is in considerable demand and is now being republished by UCL Press.